1998
DOI: 10.1002/hep.510270415
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infection is associated with increased inflammation and severe bile duct damage in rat liver allografts

Abstract: It has been suggested that cytomegalovirus (CMV) infection is involved in allograft rejection. In liver transplantation, it has been suggested that CMV is associated with the development of vanishing bile duct syndrome (VBDS), and persistent CMV has been found in liver grafts that develop chronic rejection. In this experimental study, the effect of rat CMV (RCMV) infection on intragraft changes was investigated in a rat model of acute liver allograft rejection. Liver transplantations were performed in a rat st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 37 publications
2
42
0
Order By: Relevance
“…Neither was the difference explained by the numbers of macrophages/Kupffer cells in the two groups. We have previously shown that expression of VCAM-1 is up-regulated by CMV in the sinusoidal endothelium in this model [13]. VCAM-1 has been shown to be important for monocyte extravasation [9].…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Neither was the difference explained by the numbers of macrophages/Kupffer cells in the two groups. We have previously shown that expression of VCAM-1 is up-regulated by CMV in the sinusoidal endothelium in this model [13]. VCAM-1 has been shown to be important for monocyte extravasation [9].…”
Section: Discussionmentioning
confidence: 64%
“…Concomitant CMV infection led to further increase in COX-2 expression. We have previously shown that CMV increases inflammation and graft damage in this model of acute liver allograft rejection [13]. The pattern of COX-2 induction was different in the CMVinfected and uninfected groups undergoing rejection, although in both groups there was vigorous alloresponse.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…86,102 After liver transplantation, CMV increases inflammation in the graft and the expression of class II molecules adhesion molecules critical or T-cell activation. [103][104][105] Despite adequate treatment to resolve viremia, CMV DNA may persist in hepatocytes and bile duct epithelium. 106 As such, successful antiviral treatment of CMV infection does not exclude the persistence of the virus and the risk of chronic rejection.…”
Section: Cytomegalovirusmentioning
confidence: 99%